PENGARUH LEVERAGE, LIKUIDITAS, PERPUTARAN MODAL KERJA, DAN PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Pertambangan di BEI Tahun 2014 s.d 2016) - Isty Riani; Kirmizi Kirmizi; Azwir Nasir (PEKBIS, 2019)
High profitability reflects the company's ability to generate profits through itsoperational activities. Conversely, low profitability reflects the company's operationalactivities that are not good so that the company's ability to generate profits is low.2015 was a difficult time for national mining companies, where there were severalcompanies that experienced a decline in profitability. The purpose of this study wasto determine the effect of leverage, liquidity, working capital turnover and total assetturnover influencing profitability in mining companies listed on the Stock Exchange in2014-2016 with the size of the company as a moderating variable. The population inthis study are mining companies listed on the Indonesia Stock Exchange (IDX) in2014 to 2016, which amounted to 40 companies. The samples in this study were 31companies with sampling techniques using purposive sampling. Types of data arequantitative data and secondary data sources. The hypothesis testing model of dataanalysis in this study is the Moderated Regression Analysis model. The resultsshowed: Leverage, liquidity, and asset turnover affect profitability, liquidity affectsprofitability, while working capital turnover does not affect profitability. Company sizemoderates the influence of leverage, and the effect of asset turnover on profitability.But the size of the company is not able to moderate the influence of liquidity, and theeffect of asset turnover on profitability.